A trustworthy, reliable and lightweight privacy and data integrity approach for the internet of things - Rahim Khan; Jason Teo; Mian Ahmad Jan; Sahil Verma; Ryan Alturki; Abdullah Ghani (Institute of Electrical and Electronics Engineers, 2022)
Data integrity and authenticity are among the key challenges faced by the interacting devices of Internet of Things (IoT). The resource-constrained nature of sensor-embedded devices make it even more difficult to design lightweight security schemes for these networks. In view of limited resources of the IoT devices, this paper proposes a lightweight and trustworthy device-to-server mutual authentication scheme for edge-enabled IoT networks. Initially, a trusted authority (TA) generates and assigns identities (IDs) and mask them to servers and clients, also known as member devices, in an off-line phase. These IDs are utilized to prevent possible infiltration of the adversary device(s). Next, every device ensures the authenticity of requesting devices using a sophisticated challenge, which is encrypted using a 128-bits secret key, λi. Each device expects a reply from the intended destination device for resolving the encrypted challenge within the defined time-frame, i.e.,△T. Moreover, authenticity of the requesting device is verified through the stored IDs which are shared in the off-line phase. Simulation results have verified the exceptional performance of the proposed authentication scheme against field proven approaches in terms of computational and communication costs, respectively.